2012
DOI: 10.4000/geomorphologie.9990
|View full text |Cite
|
Sign up to set email alerts
|

L’influence des actions anthropiques dans l’évolution historique d’un littoral sableux à forte dérive sédimentaire : la baie de Port-Bouët (Abidjan, Côte d’Ivoire)

Abstract: L'influence des actions anthropiques dans l'évolution historique d'un littoral sableux à forte dérive sédimentaire : la baie de Port-Bouët (Abidjan, Côte d'Ivoire)The influence of anthropic actions in the historical coastal evolution of a sandy coast with high sediment drift: the Bay of Port-Bouet (Abidjan, Ivory Coast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
(3 reference statements)
1
3
0
10
Order By: Relevance
“…According to the authors of [14], significant changes in the position of the coastline of the Wouri estuary were observed at the entrance to the estuary, namely the "Cape Cameroon" area, because it experienced a coastal retreat of more than 300 m for 30 years between 1986-2015. This dominance of variation by erosion in the area of the mouth has also been observed in other places in the world [40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 71%
“…According to the authors of [14], significant changes in the position of the coastline of the Wouri estuary were observed at the entrance to the estuary, namely the "Cape Cameroon" area, because it experienced a coastal retreat of more than 300 m for 30 years between 1986-2015. This dominance of variation by erosion in the area of the mouth has also been observed in other places in the world [40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 71%
“…Although many studies have revealed particular human impacts on the CA [6,[26][27][28], Newton et al [29] grouped all of them in nine "syndromes" (references integrate studies describing each one in particular): (1) sediment syndrome [5,8,15,28,30]; (2) water syndrome [8,31,32];…”
Section: The Human Pressure On the Camentioning
confidence: 99%
“…Amongst the coastal areas that are particularly at risk of climate change, those located on the Gulf of Guinea in West Africa rank very high [13,14]. According to Touré et al [15]; the West African coasts are undergoing a significant erosive process, which can be impressive in some places with average retreats exceeding 10 m per year. The city of Cotonou, the economic capital of Benin, is built on alluvial sand with a maximum thickness of 4 m [4] between Lake Nokoue in the North and the Gulf of Benin 1 in the South (Fig.…”
Section: Introductionmentioning
confidence: 99%